2019
DOI: 10.1128/mbio.01464-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Persistence of Chlamydia trachomatis Sexually Transmitted Strains Involves Novel Mutations in the Functional αββα Tetramer of the Tryptophan Synthase Operon

Abstract: Clinical persistence of Chlamydia trachomatis (Ct) sexually transmitted infections (STIs) is a major public health concern. In vitro persistence is known to develop through interferon gamma (IFN-γ) induction of indoleamine 2,3-dioxygenase (IDO), which catabolizes tryptophan, an essential amino acid for Ct replication. The organism can recover from persistence by synthesizing tryptophan from indole, a substrate for the enzyme tryptophan synthase. The majority of Ct strains, except for reference strain B/TW-5/OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 71 publications
(85 reference statements)
2
30
0
Order By: Relevance
“…IFN-γ has a dual function of inhibiting the growth of CT (110) in mice and inducing Th1 immune responses in CT-infected women (111). Studies have shown that IFN-γ activates host cells to restrict intracellular growth of CT by induction of IDO (112), as shown in Figure 3. The depletion of tryptophan by IDO has been proved to deprive CT of 5-hydroxytryptophan, which is essential for its differentiation into an infectious elementary body (112,113).…”
Section: Immune Response Induced By Chlamydia Trachomatismentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ has a dual function of inhibiting the growth of CT (110) in mice and inducing Th1 immune responses in CT-infected women (111). Studies have shown that IFN-γ activates host cells to restrict intracellular growth of CT by induction of IDO (112), as shown in Figure 3. The depletion of tryptophan by IDO has been proved to deprive CT of 5-hydroxytryptophan, which is essential for its differentiation into an infectious elementary body (112,113).…”
Section: Immune Response Induced By Chlamydia Trachomatismentioning
confidence: 99%
“…Studies have shown that IFN-γ activates host cells to restrict intracellular growth of CT by induction of IDO (112), as shown in Figure 3. The depletion of tryptophan by IDO has been proved to deprive CT of 5-hydroxytryptophan, which is essential for its differentiation into an infectious elementary body (112,113). If IFN-γ is removed from the host cell, tryptophan synthesis will subsequently recover, and CT quickly forms into an infectious elementary body (114).…”
Section: Immune Response Induced By Chlamydia Trachomatismentioning
confidence: 99%
“…We read with interest the recent paper by Somboonna and colleagues, addressing changes to tryptophan synthase in a single Chlamydia trachomatis strain that had an aberrant growth phenotype in vitro (1). This strain was isolated four times, over 4 years, from a patient who was apparently persistently infected.…”
Section: Lettermentioning
confidence: 99%
“…Mutations in trpR (A), trpB (B), and trpA (C) in five persistent strains from patients in sexual health clinics in King County, Washington (patients 1, 2, 3, 6, and 7) discussed in reference 2 and the F/I strain discussed in reference 1. The figure is formatted similarly to data in reference 1. Positions in each coding sequence are indicated at the top of each panel (the numbers are centered on the base), and amino acid sequence and changes are indicated below each DNA sequence.…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation